2014
DOI: 10.7196/samj.7243
|View full text |Cite
|
Sign up to set email alerts
|

Determinants, outcomes and costs of ceftriaxone v. amoxicillin-clavulanate in the treatment of community-acquired pneumonia at Witbank Hospital

Abstract: Background. Community-acquired pneumonia (CAP) is a major cause of death and morbidity worldwide. Treatment is centred on antibiotics with ceftriaxone and amoxicillin-clavulanate being some of the most commonly prescribed agents. Objective. To compare treatment outcomes and costs in patients receiving either of these two antibiotics at Witbank Hospital (WH). Methods. A total of 200 randomly selected adult patient files (100 receiving ceftriaxone and 100 amoxicillin-clavulanate) recording a diagnosis of CAP wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…The clinical cure rate also showed no significant difference between the two antibiotics. In addition, no significant difference was found between ceftriaxone and β-lactam/β-lactamase inhibitor combinations in the treatment of CAP [ 23 , 24 ], which is consistent with our findings. Preliminary meta-analysis with limited data shows no difference in clinical effectiveness.…”
Section: Discussionsupporting
confidence: 92%
“…The clinical cure rate also showed no significant difference between the two antibiotics. In addition, no significant difference was found between ceftriaxone and β-lactam/β-lactamase inhibitor combinations in the treatment of CAP [ 23 , 24 ], which is consistent with our findings. Preliminary meta-analysis with limited data shows no difference in clinical effectiveness.…”
Section: Discussionsupporting
confidence: 92%
“…A similar result was obtained on days 4 and 7 in the MITT population (p = 0.018, 0.007). It has been reported that there is no significant difference between β-lactam/β-lactamase inhibitor combinations and third-generation cephalosporins in the treatment of CAP [13][14][15][16]. However, most of those previous reports were retrospective studies, except for one that, unfortunately, did not undertake a direct comparison between β-lactam/β-lactamase inhibitor combinations and third-generation cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…The following clinical data were evaluated on admission: vital signs, comorbidities, physical examination findings, prior antibiotic treatment, and allergy to antibiotics. To evaluate the effects of treatment, clinical findings, chest radiography findings, and laboratory test results were collected before, during, and at end of treatment (EOT; days [7][8][9][10][11][12][13][14]. The late response to treatment was evaluated at end of study (EOS; days [28][29][30][31][32][33][34][35].…”
Section: Clinical and Bacteriological Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation